The Students’ Perspectives on Using ChatGPT in English Lexical Class Tasks at SMA Negeri 2 Pematangsiantar - Arisdani Elman Situmorang; Dumaris Dumaris; E Silalahi (Jurnal Pendidikan Bahasa, 2025)
This study explores students’ perspectives on using ChatGPT for English lexical class tasks at SMA Negeri 2 Pematangsiantar, highlighting the integration of AI technology in education. Utilizing qualitative research methods, data were collected through questionnaires focusing on three aspects: attractiveness, accessibility, and effectiveness. The findings reveal that students generally view ChatGPT positively, particularly appreciating its user-friendly nature and flexibility, with 71.4% expressing enthusiasm for using it to learn new vocabulary. However, perceptions of its effectiveness are more cautious, as many students remain neutral regarding its impact on their understanding and practical application of vocabulary. While 51.5% agree that ChatGPT aids in comprehension, a significant portion expresses skepticism about its overall effectiveness, indicating a need for enhancements. The study aligns with previous research that underscores AI's potential benefits in education, such as personalized learning and improved engagement. Ultimately, these findings suggest that while ChatGPT serves as a valuable educational tool, ongoing development is essential to maximize its effectiveness and foster students’ confidence in their learning outcomes, emphasizing the importance of blending technology with traditional teaching methods for a more engaging learning environment.